High Frequency Acoustics in Colloid-Based Meso- and Nanostructures by Spontaneous Brillouin Light Scattering - Still, Tim.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The present thesis deals with the exploration of phononic properties of meso- and nanostructured colloid-based composite materials at hypersonic (GHz) frequencies. The emerging field of phononics, the mechanical analogue of photonics, treats the propagation and manipulation of acoustic waves in structured materials. Due to their widely tunable properties (size, density, etc.) and their ability to self-assembly, polymer colloids are ideal systems to realize hypersonic phononics, which are investigated by Brillouin light scattering herein. Therefore, both the mechanical and physical properties of the individual colloidal particles, which manifest in their resonance vibrations (eigenmodes), as well as the acoustic propagation in colloidal structures have been investigated.
Basics and Brillouin Light Scattering -- Methods -- The Vibrations of Individual Colloids -- Phononic Behavior of Colloidal Systems -- Smaller than Colloids: Characterization of Stable Organic Glass -- Concluding Remarks -- Appendix: Scattering Geometry.
Keywords: Chemistry; Polymers; Acoustics; Nanotechnology; Surfaces (Physics).; Chemistry; Polymer Sciences; Nanotechnology; Acoustics; Characterization and Evaluation of Materials; Nanoscale Science and Technology